Pengaruh Media Pembelajaran terhadap Semangat Belajar Mahasiswa Unversitas Pamulang - Rika Amalia; Subita Candra Maulana (Institut Teknologi dan Bisnis (ITB) Semarang, 2025)
This study aims to identify the effect of learning motivation and e-learning media on the learning achievement of Pamulang University students. The method used is quantitative research with data collection techniques through questionnaires, involving 100 students from the Faculty of Economics and Business as samples. The results showed that e-learning learning media had a significant effect on student learning motivation. Regression analysis showed a coefficient of determination (R²) value of 0.496, which means that 49.6% of the variation in learning motivation can be explained by the e-learning variable.. The normality test shows that the data is normally distributed with an Asymp.Sig. value of 0.200. The t-test shows that e-learning has a positive and significant effect on learning motivation, with a significance value of 0.000. The conclusion of this study is that the use of e-learning learning media significantly increases the learning motivation of Pamulang University students, mainly due to the time flexibility offered.